A Procedure for the Retrofitting of Large-Scale Heat Exchanger Networks for Fixed and Flexible Designs applied to Existing Refinery Total Site - L. Cucek; V. Mantelli; J.Y. Yong; P.S. Varbanov; J.J. Klemeš; Z. Kravanja (Chemical Engineering Transactions, 2015)
This contribution presents the application of a novel three-step procedure for the retrofitting of large-scale heat exchanger networks (HENs) under fixed and flexible designs of existing Total Sites (TS). The entire procedure for HEN retrofitting within the analysed industrial TS consists of three steps: i) targeting and identification of the potential for improvement; ii) identification and selection of feasible and profitable alternatives for modifications, and iii) performing detailed HEN retrofit designs on the reduced spaces of alternatives. The search for retrofit modifications was performed by the economic objective by considering trade-offs between investment cost (heat exchanger area and piping) and savings in energy cost. The first targeting and second pre-screening steps were performed using the software tool TransGen, and the third synthesis step using software tool HENSYN. The novel three-step procedure was applied on an existing refinery TS.